Digital Holga Photography : Boosting Your Creativity with Holga Lenses - Correll, Robert (Peachpit Press, 2014)
Holga photography typically features soft focus, vignetting, and visible noise-traits that photographers often seek to avoid in pursuit of traditional digital photography. But these traits also define the unique character of Holga cameras and lenses, which offer a style that is retro-cool, artistic yet not pretentious-and often, a lot of fun. In this ebook, photographer Robert Correll provides an overview of Holga photography, featuring the Digital Holga SLR lens used with various attachments, such as telephoto and wide-angle, and close-up and macro lens sets. With his friendly and knowledgeable voice, he walks you through the basics of how to use the quirks of the Holga to your advantage, and includes several examples that illustrate the creativity at your fingertips when using the camera. Follow along with Robert and you will: Learn how to handle Holga lenses, selecting camera modes, using Live View to monitor your lighting and compose your shots, focusing the lens, reviewing your shots, and making adjustments as you go. Have fun with more advanced techniques, shooting close-ups and macros, using flash, experimenting with lighting, and making movies. Process your own images by performing RAW processing and exploring your options in terms of exposure, color vibrance and saturation, vignetting, and contrast.